Social Media : Towards Integration of New Media in the Promotion Mix - Drugge, Arvid (2014)
There has been extensive research on social media and its effects over the last decade including: its effect on business to consumer communication, its effect on how consumers seek and receive information. It is also renowned for the research on its inherent ability to spread word-of-mouth at exponential rates and its effects on creating and maintaining relationship. The purpose of this thesis is to determine businesses current attitudes toward social media usage for promotional use. To determine if businesses are jumping half-informed onto the social media bandwagon due to popular opinion, or the opposite. Furthermore another intention of this thesis is to provide tutoring material for businesses that are currently non-users of social media. As social media currently lacks a textbook description as other older promotion tools such as traditional Advertising. In response this thesis has instead relied on some of the most reoccurring researched characteristics, namely those above in order to create theoretical Frame of Reference as well as describing social media compared to traditional media, its mechanics, the five current main social media platform, why users and businesses use or should use social media and finally the risks associated with the media. This thesis has taken a deductive, qualitative and multiple case study analysis of three businesses that utilizes social media in their promotion mix in order to ascertain: (RQ1) How businesses have integrated social media outlets into their marketing? (RQ2) How businesses have decided to integrate social media into their marketing efforts? (RQ3) How businesses perceive social media in their marketing efforts? As well as, (RQ4) what marketing attributes have businesses credited social media? The businesses interviewed for this thesis were chosen due to them enjoying a reputation as pioneers among their peers in Luleå to make the most of social media in a promotional context. And as such serves as one of several actions to strengthen the validity and reliability ...